Current Challenges in Revenue Mobilization : Improving Tax Compliance. (Policy Papers; Policy Paper, 2015)
This paper addresses core challenges that all tax administrations face in dealing with noncompliance-which are now receiving renewed attention. Long a priority in developing countries, assuring strong compliance has acquired greater priority in countries facing intensified revenue needs, and is critical for fairness and statebuilding. Series: Policy Papers.